Sarcopenia is associated with reduced survival in patients with advanced hepatocellular carcinoma undergoing sorafenib treatment - Antonelli, Giulio (United European Gastroenterol J, 2018)
BACKGROUND: Sarcopenia has been associated with poor outcomes in patients with cirrhosis and solid tumours. OBJECTIVE: Analyse the influence of sarcopenia on survival and treatment duration in patients with advanced hepatocellular carcinoma (HCC) treated with sorafenib. METHODS: We conducted a multicentre, retrospective study on 96 patients with advanced HCC treated with sorafenib, all with available abdominal computed tomography (CT) scan within 30 days from treatment start. Anthropometric, laboratory, treatment and follow-up data were collected. Sarcopenia was defined by reduced skeletal muscle index calculated from an L3 section CT image. RESULTS: Sarcopenia was present in 49% of patients. Patients were divided into two groups according to sarcopenia: age was significantly higher in the sarcopenic group (SG) (66 years (31–87) versus 72 years (30–84), p = 0.04], with no difference in other baseline characteristics. The SG showed shorter overall survival (OS) (39 (95% confidence interval (CI) 26–50) versus 61 (95% CI 47–77) weeks (p = 0,01)) and shorter time on treatment (12.3 (95% CI 8–19) versus 25.9 (95% CI 15–33) weeks (p = 0.0044)). At multivariate analysis, sarcopenia was independently associated to reduced OS (p = 0.03) and reduced time on treatment (p = 0.001). CONCLUSION: Sarcopenia is present in almost half of patients with advanced HCC, and is associated with reduced survival and reduced duration of oral chemotherapy.